2022
DOI: 10.24269/iso.v6i1.1035
|View full text |Cite
|
Sign up to set email alerts
|

Persepsi Keamanan, Kepercayaan, dan Akuntabilitas Perusahaan Terhadap Niat Berdonasi Melalui Fintech Crowdfunding

Abstract: This study aims to empirically examine the effect of perceived security, trust and corporate accountability on the intention to donate through fintech crowdfunding. This research data is primary data which is obtained by distributing questionnaires through google form. The population of this study is all Indonesian people who have used fintech crowdfunding. The sample in this study used simple random sampling, where everyone who has used fintech crowdfunding is randomly selected and asked to be part of the res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
0
0
Order By: Relevance
“…In the context of charitable donations and fundraising, research conducted in China has shown that trust has a substantial and positive impact on an individual's intention to contribute to charitable projects via fundraising platforms (Li et al, 2018) Similarly, Salsabila and Hasbi (2021) found that trust played a significant role in fundraising activities on the Kitabisa, a crowdfunding platform in Indonesia and so for Mahad et al (2015) on Malaysia mobile banking applications. It is worth noting that trust in using a digital service can have an even more pronounced influence when coupled with strong security measures and company accountability (Irawan et al, 2022). However, it is important to acknowledge that findings can vary across different studies and contexts.…”
Section: Hypotheses Of Studymentioning
confidence: 99%
“…In the context of charitable donations and fundraising, research conducted in China has shown that trust has a substantial and positive impact on an individual's intention to contribute to charitable projects via fundraising platforms (Li et al, 2018) Similarly, Salsabila and Hasbi (2021) found that trust played a significant role in fundraising activities on the Kitabisa, a crowdfunding platform in Indonesia and so for Mahad et al (2015) on Malaysia mobile banking applications. It is worth noting that trust in using a digital service can have an even more pronounced influence when coupled with strong security measures and company accountability (Irawan et al, 2022). However, it is important to acknowledge that findings can vary across different studies and contexts.…”
Section: Hypotheses Of Studymentioning
confidence: 99%